Lives in fiction: Auto/biographies as theoretical narratives - Erasga, Dennis S. (Animo Repository, 2014)
Sociological imagination is an open invitation to theorize from the stories we tell about ourselves and others. More than self-expression, the sociological ethos of auto/biographical narration is to extend the reality of a solipsistic and exclusive existence into a common and public experience. In order to achieve this, the narrator must convert biographies into scribed realities. The narrating process, however, has unique epistemic anchorage (memory-based) and stylistic requirement (literary) that encage lived lives in a fictional genre, giving this mode of writing a unique interpretive lens that projects new visions of the social. Consequently for theorizing purposes, auto/biographies are meaning-claims that should no longer be read exclusively in terms of their dramatic and documentary values, but more in terms of their theoretical affordances. This paper explores the implications and utility of fictionalized auto/biographical narratives in expanding the ambit of sociological theorizing. © 2014 by De La Salle University.